Enhancing the antitumor effect of methotrexate in intro and in vivo by a novel targeted single-walled carbon nanohorn-based drug delivery system. Issue 53 (13th May 2016) - Wang, Ran; Cui, Hongjing; Wang, Junling; Li, Nannan; Zhao, Qian; Zhou, Ying; Lv, Zhiyi; Zhong, Wenying
Abstract : The present research reports a smart multifunctional oxidized single-wall carbon nanohorns (oxSWNHs) drug delivery system (DDS) which could enhance the anti-tumor effect of methotrexate (MTX). Abstract : The present research reports a smart multifunctional oxidized single-wall carbon nanohorns (oxSWNHs) drug delivery system (DDS) which could enhance the anti-tumor effect of methotrexate (MTX). In this DDS (MTX@oxSWNHs–PEG–Tf), oxSWNHs loaded MTX was wrapped with DSPE–PEG–NH2 to prolong blood circulation half-life and target tumors with the help of covalent grafting of transferrin (Tf). The obtained DDS was characterized by scanning electron microscopy, UV-vis spectrophotometry, size distribution analysis and Z -potential measurement. Cell uptake studies on MAD-MB-231 and HepG2 cell lines confirmed that the MTX@oxSWNHs–PEG–Tf exerted higher antitumor activity compared with free drug or non-targeted counterpart. The in vivo antitumor efficacy of MTX@oxSWNHs–PEG–Tf was much stronger than that of the free drug group by comparing the change of tumor volume and weight. Toxicity studies showed little perceivable cardiotoxicity, hepatotoxicity and pulmonary toxicity of MTX@oxSWNHs–PEG–Tf, indicating that this new tumor-targeting DDS significantly enhanced the anti-tumor effect of MTX and decreased its side effects.